The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1523/jneurosci.5388-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Malleability of Spike-Timing-Dependent Plasticity at the CA3-CA1 Synapse

Abstract: The magnitude and direction of synaptic plasticity can be determined by the precise timing of presynaptic and postsynaptic action potentials on a millisecond timescale. In vivo, however, neural activity has structure on longer timescales. Here we show that plasticity at the CA3-CA1 synapse depends strongly on parameters other than millisecond spike timing. As a result, the notion that a single spiketiming-dependent plasticity (STDP) rule alone can fully describe the mapping between neural activity and synapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

46
428
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 296 publications
(478 citation statements)
references
References 60 publications
46
428
3
1
Order By: Relevance
“…Recent experiments conducted in acute hippocampal slices, which closely approximate the conditions present in vivo, have demonstrated that the plasticity of CA3-CA1 synapses is jointly dependent upon the temporal offset of pre-and post-synaptic firing, number of post-synaptic spikes fired, frequency of spike pairings, and duration of stimulation [28][29][30]. Firstly, we aim to ascertain whether the Calcium control hypothesis -which has been demonstrated to successfully reproduce earlier STDP data obtained in culture (Figure 1a), as well as that induced by other activity patterns -can be revised to account for this joint dependency [18,[41][42][43][44][45][46][47][48].…”
Section: Induction Of Synaptic Plasticity By Spike-timing Stimulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent experiments conducted in acute hippocampal slices, which closely approximate the conditions present in vivo, have demonstrated that the plasticity of CA3-CA1 synapses is jointly dependent upon the temporal offset of pre-and post-synaptic firing, number of post-synaptic spikes fired, frequency of spike pairings, and duration of stimulation [28][29][30]. Firstly, we aim to ascertain whether the Calcium control hypothesis -which has been demonstrated to successfully reproduce earlier STDP data obtained in culture (Figure 1a), as well as that induced by other activity patterns -can be revised to account for this joint dependency [18,[41][42][43][44][45][46][47][48].…”
Section: Induction Of Synaptic Plasticity By Spike-timing Stimulationmentioning
confidence: 99%
“…The experimental data we aim to replicate can be characterised by considering the effects of two different stimulation protocols -pairing 100 single preand post-synaptic spikes (hereafter referred to as 'spike pairing') at low frequencies (0.1-5Hz), which generates a depression-only learning rule ( Figure 1b); or pairing a single pre-synaptic spike with two post-synaptic spikes (hereafter referred to as 'triplet pairing'), which generates a triphasic bidirectional learning rule after 100 pairings at a frequency of 5Hz (Figure 1c), an unsaturated potentiation-only rule after 30 pairings at 5Hz (Figure 1d), or mild depression after 100 pairings at a frequency of 0.5Hz (data not shown). Each of these data sets can be fitted by a learning rule composed of Gaussian (or a sum of Gaussian) curves centred at short, positive temporal offsets [29]. [26] and (b-d) acute slice preparations [29].…”
Section: Induction Of Synaptic Plasticity By Spike-timing Stimulationmentioning
confidence: 99%
See 3 more Smart Citations